تصورات الطلبة من ذوي الاحتياجات الخاصة - جديدي, سيف الدين (جامعة الوادي University of Eloued, 2018)
هدفت هذه الدراسة إلى التعرف على تصورات الطلبة من ذوي الاحتياجات الخاصة"ذوي الإعاقة السمعية وذوي الإعاقة البصرية" لمدى تطبيق معايير إدارة الجودة الشاملة بجامعة قسنطينة 2 عبد الحميد مهري،وكانت عينة هذه الدراسة 10 طلبة من ذوي الإعاقة السمعية وذوي الإعاقة البصرية. وقد استخدم المنهج الوصفي الاستكشافي كمنهج مناسب لهذه الدراسة،والمقابلة النصف موجهة،والاستبيان كأداة لهذه الدراسة،وبعد معالجة بيانات الدراسة ونتائجها،ومناقشة الفرضيات،اسفرت الدراسة على النتائج التالية: -تطبق معايير إدارة الجودة من وجهة نظر الطلبة من ذوي الاحتياجات الخاصة"من ذوي الإعاقة السمعية و البصرية" بالمؤسسة الجامعية عبد الحميد مهري بقسنطينةبنسبة اقل من 50%،محققة جزئيا وذلك لتحقق الفرضيات الجزئية الثلاثة بإستثناء الفرضية الجزئية الثانية والتي تنص على تطبيق معيار تطوير طرائق التدريس. This study aims to identify the expectations of students with special needs “those with hearing or visual disabilities" about the application of quality management standards at the University of Constantine 2 Abdelhamid Mehri, where this study was applicated over 10 students with hearing or visual disabilities. The descriptive approach was used as a method in this study, also the semi-guided interview and the questionnaire where used as a tool, After processing the data of the study and its results and then discussing the hypotheses ,the results where as follows: The quality management standards according to the expectations of students with disabilities "with hearing or visual disabilities" at the University Abdelhamid Mehri, Constantine is applied by less than 50%.So the general hypothesis is partially realized because all the partial hypotheses are realized except for number two.
مقال
Keywords: معايير نظام إدارة الجودة,مؤسسات التعليم العالي,ذوي الإحتياجات الخاصة .الإقاعة السمعية والبصرية; quality management system standards; universities; Students with special needs with hearing and visual disabilities.